THE INDEPENDENCY OF THE INSTITUTION FOR THE PROTECTION AND THE ESTABLISHMENT OF HUMAN RIGHTS TOWARDS THE GLOBALIZATION ERA 2020 - Khalid Khalid (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
The process of globalization continues to roll and will enter the year 2020, not only the problem of economic life, but has been plagued in the globalization of politics, defense and security, science and technology, social, cultural, and legal. Globalization in politics can not be separated from the movement of human rights, transparency and democratization. Globalization in the movement of human rights, then Indonesia must incorporate human rights instruments internationally recognized by UN countries into the positive law of national accordance with Indonesian culture by strengthening the institutions of protection and the enforcement of human rights, institution of study, and the wider community to play a role in promote and protect human rights on the lives of the peoples of Indonesia. Quite whether or not the recognition and the protection of the rights of citizens does not necessarily only by ratifying and many articles regulating rights of citizens, but the constitution still must be written with clear and complete for the human rights of citizens, the most important thing then is the political will and consistency run those chapters in the behavior of national and state level, and this can not be released necessity of institutions that maintain, run and oversee the realization of the recognition, protection and enforcement of human rights. Keywords: Institutional Independence, Protection and Enforcement of Human Rights, Globalization Era.